2016
DOI: 10.1007/s10456-016-9523-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lymphangiogenesis in the diaphragm by macrophages and VEGFR-3 signaling

Abstract: Lymphatic vessels play important roles in fluid drainage and in immune responses, as well as in pathological processes including cancer progression and inflammation. While the molecular regulation of the earliest lymphatic vessel differentiation and development has been investigated in much detail, less is known about the control and timing of lymphatic vessel maturation in different organs, which often occurs postnatally. We investigated the time course of lymphatic vessel development on the pleural side of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…In addition, Cx43 expression in thymic regulatory T cell precursors enhances the production of Foxp3 + regulatory T cells (Kuczma et al 2011), a population of cells which were recently shown to modulate lymphedema and promote lymphatic vessel function (Gousopoulos et al, 2016). During development, lymphangiogenesis in the diaphragm is regulated by macrophages, which are closely associated with the sprouting tips of lymphatic vessels (Ochsenbein et al, 2016). However, macrophages associated with lymphangiogenesis are typically LYVE-1 positive (Kim et al, 2007; Ochsenbein et al, 2016) and therefore Cx43 in those macrophages may be deleted in Cx43 ΔLEC mice, but this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cx43 expression in thymic regulatory T cell precursors enhances the production of Foxp3 + regulatory T cells (Kuczma et al 2011), a population of cells which were recently shown to modulate lymphedema and promote lymphatic vessel function (Gousopoulos et al, 2016). During development, lymphangiogenesis in the diaphragm is regulated by macrophages, which are closely associated with the sprouting tips of lymphatic vessels (Ochsenbein et al, 2016). However, macrophages associated with lymphangiogenesis are typically LYVE-1 positive (Kim et al, 2007; Ochsenbein et al, 2016) and therefore Cx43 in those macrophages may be deleted in Cx43 ΔLEC mice, but this remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…During development, lymphangiogenesis in the diaphragm is regulated by macrophages, which are closely associated with the sprouting tips of lymphatic vessels (Ochsenbein et al, 2016). However, macrophages associated with lymphangiogenesis are typically LYVE-1 positive (Kim et al, 2007; Ochsenbein et al, 2016) and therefore Cx43 in those macrophages may be deleted in Cx43 ΔLEC mice, but this remains to be determined. Cx43 could also play a role in chemokine signaling during lymphatic vessel development, with this pathway being altered in Cx43 −/− mice but not Cx43 ΔLEC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Csf1 op/op mice survive for longer periods than Csf1r −/− mice, and the functional consequences of this mutation have been studied in more detail. Csf1 op/op mice have reduced weight, low growth rate, extensive skeletal abnormalities, hearing, vision and olfactory deficits, abnormal intestinal organization, Paneth cell deficiency, infertility, reduced mammary gland development, altered angiogenesis and lymphangiogenesis and altered neurogenesis (Kondo et al, 2013; Ochsenbein et al, 2016; reviewed in Arnold & Betsholtz, 2013; Chitu, Caescu, et al, 2015; Chitu et al, 2016; Harvey & Gordon, 2012; Pollard, 2009; Pollard & Stanley, 1996). CSF-1 regulates tissue development through its action on both hematopoietic (macrophages and osteoclasts) and nonhematopoietic cells.…”
Section: Csf-1-regulated Macrophages In Tissue Morphogenesis and Omentioning
confidence: 99%
“…Finally, we tested the potential of the assay in an anatomical location of the mouse where it is difficult to visualize the lymphatic outflow using in vivo optical methods. We chose the peritoneal cavity, as many different outflow routes have been described including uptake through stomata in the diaphragm and by omental lymphatics of the abdomen (19,(24)(25)(26). After i.p.…”
Section: K14-vegfr-3-fc Mice Lacking Dermal Lymphatic Vessels Show Esmentioning
confidence: 99%